On the Existence of Three Positive Solutions for a Caputo Fractional Difference Equation - Lili Kong; Huiqin Chen; Luping Li; Shugui Kang (Discrete Dynamics in Nature and Society)
In this paper, we introduce the application of three fixed point theorem by discussing the existence of three positive solutions for a class of Caputo fractional difference equation boundary value problem. We establish the condition of the existence of three positive solutions for this problem.